(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
This article argues that theatre as an apparatus of change has for a long time privileged thetransformation of the oppressed people by inciting their conscience and consciousness. This incitement is meant to make them takeaction, leading to some kind of social and political agency. However, thisarticle argues that the oppressor equally needs to be changed. Therefore theatre/dramaas a tool of intervention should be framed in such a way that it providespossibilities for the oppressor to change instead of acting as an imaginarythat only privileges the vanquishing of the oppressor. Thearticle takes recourse in John OToolesexperiment with theatre in education process to advance its arguments in regard to Bole Butakes drama andspecifically his play „Family Saga.